Implementasi Penguatan Profil Pelajar Pancasila (P5) Pada Kurikulum Merdeka di Kelas IV SD Inpres Ende 14 - Rando, Agnes Remi; Witak, Katarina Kidik (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2024)
The aim of this research will be to discuss the implementation of the Project for Strengthening the Profile of Pancasila Students (P5) and the supporting and inhibiting factors during the implementation of the Project for Strengthening the Profile of Pancasila Students (P5) in the Independent Curriculum at SD Inpres Ende 14 as well as the results of the Implementation of Strengthening the Profile of Pancasila Students (P5) In the Independent Curriculum at SD Inpres Ende 14. Data collection techniques use observation, interviews and documentation. The results of the research show that (1) Analysis of the Implementation of the Project for Strengthening the Profile of Pancasila Students (P5) in the Independent Curriculum at SD Inpres Ende 14. (2) Supporting factors for the implementation of the Project for Strengthening the Profile of Pancasila Students (P5) in the Independent Curriculum at SD Inpres Ende 14 come from Collaboration between school members that supports project-based learning, as well as support from external parties to realize international standard-based projects, the obstacles that arise are the lack of project references, and (3) the result of the project's learning objectives is to realize the 6 aspects of the Pancasila Student Profile where each aspect is realized in school co-curricular learning.